The Emotional Kitchen Space Aging With Dignity Around the Kitchen Table - Wang, Guangjin (Auckland University of Technology, 2020)
How can a kitchen be designed as an elderly-friendly emotional space that encourages people to share positive social experiences of cooking and dining? How can designers support people to age with dignity? This practice-based design research is based on the strong emotional bond between me and my grandfather, and my observations of how he struggled to use his home. I have developed design principles for emotional spaces that support independence, social connection, and cultural belonging. I have focused on the kitchen as a space that poses particular challenges, and ultimately propose an Emotional Kitchen Table, a piece of furniture that could be fitted into existing apartments or houses to provide a more fulfilling spatial experience for the elderly. My methodology centers on developing empathy, and I use ideas from design ethnography (particularly personas and scenarios) and digital technologies for simulating use. My aim is to demonstrate how a concern for emotional space and empathy can help designers like myself give older people the opportunity to age with dignity.
Keywords: Emotional Design; Aging dignity; Cultural Heritage; Visualization as mood induction; Kitchen table design